Understanding the links between agriculture and health: Agriculture, Food Safety, and Foodborne diseases - Todd, Ewen C. D.; Narrod, Clare (International Food Policy Research Institute, 2006)
Millions of adults and children suffer from the ill-health effects of foodborne diseases, especially in developing countries. Owing to erratic surveillance systems, estimates of the burden of foodborne diseases are inaccurate and most likely too low. Official reports indicate relatively small numbers of reported cases. The World Health Organization estimates that annually 1.8 million people worldwide (excluding China), most of whom are children, died from diarrheal diseases caused by microbial agents largely attributed to contaminated food and water.